Cardiac rehabilitation and secondary prevention in COVID-19 times: Single center experience. (11th May 2021) - Burazor, I; Spiroski, DS; Terzic, J; Otasevic, P; Babic, R; Nikolic, A; Ilic, I; Loncar, G; Cosic, Z; Colic, M; Rihor, B; Andjic, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac rehabilitation (CR) is a class I treatment for cardiovascular disease, still, underutilization of these services remains. During the coronavirus 2019 (COVID-19) pandemic, an even greater gap in CR care has been present. Purpose and methods: We aimed to present the cardiac rehabilitation during COVID 19 times in Belgrade. At the beginning of epidemic in Serbia the number of patients in in-house city program was 70 out of 70 beds, with 200 patients who were scheduled (on the waiting list). Similarly to the other countries, we continued to admit only urgent patients with acute coronary settings. Results: Only one PPCI center in Belgrade (2 million inhabitants plus surrounding area; out of five centers) continue to admit COVID-negative patients with STEMI from 13of March to 11 of May, during the first pick of COVID-19 epidemic in Serbia. Out -patients cardiac rehabilitation programs were stopped. The totals of 80 patients (PCR negative) were transferred to exercised based cardiac rehabilitation secondary prevention program during the first pick of epidemic directly from acute hospital. The majority of patients were males in their 50s. All risk factors were noted and patients were with much less risk factors compared to non- epidemic era. Lipid profile was measured. Six minutes walking test was performed at the beginning and exercise plan was made. Unfortunately, exercise based three weeks in- house cardiac rehabilitation was completed in only 1% of patients while others quite the program. Conclusion: The COVID-19 pandemic presents a time to highlight the value of home-based models as we search for ways to continue to provide care. Standardization of home based CR models is essential to provide care for a wider range of patients and circumstances in the near future.